2019
DOI: 10.26434/chemrxiv.9122009.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cofactor-Independent Pinacolase Directs Non-Diels-Alderase Biogenesis of the Brevianamides

Abstract: <p>Fungal bicyclo[2.2.2]diazaoctane indole alkaloids demonstrate intriguing structures and a wide spectrum of biological activities. Although biomimetic total syntheses have been completed for representative compounds of this structural family, the details of their biogenesis have remained largely uncharacterized. Among them, Brevianamide A represents the most basic form within this class bearing a dioxopiperazine core structure and a rare 3-<i>spiro</i>-<i>psi</i>-indoxyl skeleto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 75 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…7B) [50]. Therefore, the preponderance of 17 over 18 is likely due to intrinsic energy barriers in the cycloaddition reaction (nonenzyme catalyzed) [52]. Through the utilization of frontier molecular orbital theory, it was predicted that, for the energy levels of a relatively electron‐rich diene (such as that in the DKP) to effectively interact with a dienophile, powerful electron‐withdrawing groups would need to be present in the dienophile.…”
Section: Enantioselective Diels–alderasesmentioning
confidence: 99%
See 4 more Smart Citations
“…7B) [50]. Therefore, the preponderance of 17 over 18 is likely due to intrinsic energy barriers in the cycloaddition reaction (nonenzyme catalyzed) [52]. Through the utilization of frontier molecular orbital theory, it was predicted that, for the energy levels of a relatively electron‐rich diene (such as that in the DKP) to effectively interact with a dienophile, powerful electron‐withdrawing groups would need to be present in the dienophile.…”
Section: Enantioselective Diels–alderasesmentioning
confidence: 99%
“…Since the prenyl group is an isolated electron‐neutral vinyl group, one would not expect the [4 + 2] cycloaddition in DKPs to be spontaneous without catalysis, but biomimetic syntheses [53] have shown that the azadiene undergoes a spontaneous IMDA to generate a mixture of brevianamides with enantiomorphic bicyclo[2.2.2] ring systems. While spontaneous, diastereocontrol of the IMDA may be impacted by upstream transformations such as the early‐stage semipinacol rearrangement to generate the 3‐spiro‐ψ‐indoxyl species [52].…”
Section: Enantioselective Diels–alderasesmentioning
confidence: 99%
See 3 more Smart Citations